Studi Komparatif Morfologi Kota Tepian Air - Herdy Pratama Putra; Slamet Trisutomo; Riekje Hehanusa Pangkarego (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Generally, the growth point of big cities in Indonesia was started from the waterfront. This fact is related to Indonesia as archipelagic country that makes its location more strategic. Makassar and Kendari is the waterfront city but have different forms. Makassar is formed by elongated coastline while Kendari formed by the bay. However, the two cities have in common as a trading city. This study use qualitative and quantitative analysis approach comparing their form to find the similarities and differences their morphology. The variable of this study consist of land use, population density, intensity of land use, urban centers and road network systems forming morphplogy of city. The result of comparison of the two cities shows population density of Makassar is greater than Kendari. Population and topography influence the hierarchy of urban centers in both cities. On the other hand, the both of cities have different in land use pattern, such as green open space, housing and industry, influenced by distance of shoreline. Building coverage ratio in the waterfront area, downtown and new development of Makassar is higher than Kendari in the same areas.